Current Status of Hard X-Ray Nano-Tomography on the Transmission Microscope at the ANATOMIX Beamline. Issue 1 (1st December 2022) - Scheel, M; Perrin, J; Koch, F; Daniel, G; Giorgetta, JL; Cauchon, G; King, A; Yurgens, V; Le Roux, V; David, C; Weitkamp, T
Abstract: The transmission X-ray microscope (TXM) on the Anatomix beamline welcomed its first nano-tomography users in 2019. The instrument is based on diffractive optics and works in the range of energies from 7 keV to 21 keV. A spatial resolution in 3D volumes of better than 100 nm can be achieved. The design allows imaging samples in air, and local tomography as well as off-axis tomography scans are possible. Scans below and above K-edges can be made to access elemental distribution. The TXM serves materials science and the bio-medical field.